2018
DOI: 10.1016/j.hemonc.2016.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Polycythemia vera masked due to severe iron deficiency anemia

Abstract: Polycythemia vera is one of the chronic myeloproliferative diseases and very few patients present with its actual clinical manifestations. The most common findings are increased red cell mass and an increased leukocyte count with decreased erythropoietin. We present a case where there was a delay in the diagnosis of polycythemia because of menorrhagia in the past. On admission, the patient presented with elevated red and white blood cell counts, erythropoietin was low, and polycythemia was then suspected. A bc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…[6][7][8] The red blood cell count (RBC) may be underutilized. 9 In addition, iron deficiency may raise suspicion for PV, 10 and the role of EPO warrants further investigation. 11,12 Key clinical parameters include smoking history and body mass index (BMI); the latter is often associated with obstructive sleep apnea (OSA).…”
mentioning
confidence: 99%
“…[6][7][8] The red blood cell count (RBC) may be underutilized. 9 In addition, iron deficiency may raise suspicion for PV, 10 and the role of EPO warrants further investigation. 11,12 Key clinical parameters include smoking history and body mass index (BMI); the latter is often associated with obstructive sleep apnea (OSA).…”
mentioning
confidence: 99%
“…Some authors previously hypothesized that mPV could be a consequence of iron deficiency in PV patients. 12 Despite thrombocythemic patient MCV was in the normal range and not different from true PV patients, we can not totally exclude in this study that the platelet increase observed for these patients could be related, at least in some cases, to iron deficiency since ferritin level was not measured systematically for all patients. However, our findings are not in favor of this hypothesis since MCV level were not lower in mPV compared to true PV.…”
mentioning
confidence: 59%
“…The hemolytic process was probably responsible for normal Hb and Ht levels and normal RCV. Although masked PV due to an iron deficiency are well‐known, masked PV due to hemolysis are uncommon and this association could be undiagnosed or misdiagnosed with another MPN. Nevertheless, a differential diagnosis between early phases of PV, ET, and PMF is necessary because of their differences according to prognosis and therapeutic management .…”
Section: Discussionmentioning
confidence: 99%